PEMBELAJARAN ENTREPRENEUSHIP DENGAN METODE DESIGN THINKING PADA SISWA SISWI SMAK FRATERAN SURABAYA - Krismi Budi Sienatra; Metta Padmalia (Universitas Pahlawan Tuanku Tambusai, 2022)
Entrepreneurship education must be carried out from an early age. The imbalance in the number of productive labor forces with the availability of jobs will cause unemployment. One way to reduce unemployment is to create entrepreneurs through entrepreneurship education from an early age. SMAK Frateran is a school that strives to create graduates who are able to answer the challenges of the future. SMA Frateran specifically makes entrepreneurship education taught from an early age through learning with gradual materials, especially with the design thinking method. The design thinking method starts with redefining the problem and creating innovative solutions for prototyping and testing. It is hoped that the design thinking method will provide entrepreneurship education learning by looking at environmental problems and solutions by making a business project as an output of learning. Keywords: entrepreneurship, entrepreneurship education, design thinking